2019
DOI: 10.1155/2019/2426313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Characteristics of Symptomatic and Asymptomatic Neurosyphilis in HIV-Negative Patients: A Retrospective Study of 264 Cases

Abstract: A retrospective study was performed to compare the differences in clinical and laboratory features of asymptomatic neurosyphilis (ANS) and symptomatic neurosyphilis (SNS). A total of 264 HIV-negative inpatients with neurosyphilis were enrolled from Beijing Ditan Hospital and Beijing Tiantan Hospital between January 2014 and May 2018, including 110 SNS and 154 ANS. The SNS group had more patients in males, older median age and without antisyphilis treatment than ANS group (P<0.001, P<0.001, and P<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Abandonment of preventive examinations means that in many patients the disease is undiagnosed. Undiagnosed early syphilis is the reason for an increased incidence of symptomatic syphilis or neurosyphilis [49,71]. Diagnosis of neurosyphilis is established on the basis of clinical signs and laboratory diagnostic tests of serum and CSF.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Abandonment of preventive examinations means that in many patients the disease is undiagnosed. Undiagnosed early syphilis is the reason for an increased incidence of symptomatic syphilis or neurosyphilis [49,71]. Diagnosis of neurosyphilis is established on the basis of clinical signs and laboratory diagnostic tests of serum and CSF.…”
Section: Diagnosismentioning
confidence: 99%
“…Zeng et al suggested that serum CXCL13 levels are not useful in support of the diagnosis of neurosyphilis in HIV-negative patients, since serum CXCL13 concentrations are similar in neurosyphilis and other neurological viral or cryptococcal infections [11]. However, patients with syphilis and HIV co-infection have been found to have higher CSF CXCL13 values than those with HIV infection only [49]. Moreover, CSF CXCL13 levels have been shown to be significantly higher in symptomatic and asymptomatic neurosyphilis in comparison to uncomplicated syphilis [52,53].…”
Section: Cxcl13 Concentrationmentioning
confidence: 99%
“…We recorded the medical history, neurological symptoms and signs, and serum and CSF laboratory testing results. According to the guidelines of NS in the USA, Europe and related literatures (14)(15)(16)(17)(18), the criteria for the diagnosis of NS in our study included positive syphilis serologies and one or more of the followings: (a) positive CSF rapid plasma regain (RPR); (b) positive CSF Treponema pallidum particle agglutination (TPPA) and fluorescent treponemal antibody absorption (FTA-ABS), with increased CSF protein (>45 mg/dl) or white blood cells (WBC) (> 5/µl) in absence of other known causes of these abnormalities. All of the enrolled patients were HIV negative.…”
Section: Patientsmentioning
confidence: 99%
“…All study participants were 18 years old or older, were diagnosed with HIV-negative neurosyphilis, and met all the following conditions: (1) Treponema pallidum particle agglutination assay (TPPA) and toluidine red unheated serum test (TRUST) titer were tested in serum and the serum TPPA was positive; (2) the serologic test was combined with TRUST positivity in CSF or a CSF white blood cell count of [ 5 cells/ll or CSF protein of [ 45 mg/dl with TPPA reactivity in the CSF; (3) other conditions that could cause neurological symptoms, such as myelopathy, were ruled out, as suggested by the European guideline on the management of syphilis [11]. Patients with NS were dichotomized into asymptomatic neurosyphilis (ANS) and symptomatic neurosyphilis (SNS) groups according to whether they had clinical complaints or not, with the ANS patients being discovered either in a premarital physical examination or accidentally [7].…”
Section: Study Patientsmentioning
confidence: 99%
“…Neuroimaging examinations in patients with NS are important for the differential clinical diagnosis and follow-up, with the presentations being diverse [6]. Although several studies have analyzed clinical and laboratory characteristics of asymptomatic and symptomatic neurosyphilis patients, to the best of our knowledge, no systematic study has investigated neuroimaging changes after anti-syphilitic treatment [7][8][9][10]. Herein, we retrospectively reviewed 102 patients with NS who were examined at our center and made comparisons between asymptomatic and symptomatic NS patients.…”
Section: Introductionmentioning
confidence: 99%